Phase IIb multicentred randomised trial of besifovir (LB80380) versus entecavir in Asian patients with chronic hepatitis B. Issue 6 (26th August 2013) - Lai, Ching-Lung; Ahn, Sang Hoon; Lee, Kwan Sik; Um, Soon Ho; Cho, Mong; Yoon, Seung Kew; Lee, Jin-Woo; Park, Neung Hwa; Kweon, Young-Oh; Sohn, Joo Hyun; Lee, Jiyoon; Kim, Jeong-Ae; et al.
Abstract : Background: Besifovir (LB80380) is an acyclic nucleotide phosphonate effective in hepatitis B virus (HBV) DNA suppression for both treatment-naive and lamivudine-resistant chronic hepatitis B (CHB) patients in preliminary studies. Design: We aimed to compare the safety and antiviral activity of two doses of besifovir (90 mg and 150 mg daily) with entecavir 0.5 mg daily in CHB patients. 114 patients were randomised to receive besifovir 90 mg daily (n=36), besifovir 150 mg daily (n=39) or entecavir 0.5 mg daily (n=39). HBV DNA and liver biochemistry, including serum L-carnitine levels, were monitored. Results: At week 48, in the intention-to-treat population, the proportion of patients achieving undetectable HBV DNA (<20 IU/mL) were 63.6%, 62.9% and 58.3%, respectively (p>0.05). The serum mean log10 HBV DNA changes from baseline for the HBeAg-positive patients were −5.84, −5.91 and −6.18, respectively; and for the HBeAg-negative patients were −4.65, −4.55 and −4.67, respectively (p>0.05). There were no differences in the proportions of patients achieving normalisation of alanine aminotransferase (91.7%, 76.9%, 89.7%, respectively) and HBeAg seroconversion (11.11%, 15%, 9.52%, respectively) among all three groups. None of the patients had resistant mutations or increase in serum creatinine of >0.5 mg/dL from baseline. 64 (94.1%) patients on besifovir had lowering of serum L-carnitine (not tested in entecavir patients). L-carnitine levels returned to normal with carnitine supplement. Conclusions: At 48 weeks, 90 mg and 150 mg daily of besifovir were non-inferior to entecavir 0.5 mg daily in treatment-naive CHB patients. The only significant side effect of besifovir was L-carnitine depletion, requiring carnitine supplementation.